Contextualization of Forest Governance for Implementation of REDD+ in Bangladesh (The Chittagong University Journal of Science, 2021)
Poor governance accelerates the deforestation and forest degradation through corruption in Bangladesh due to the enhancement of prevalent activities such as excessive collection of forests products, trafficking of logs out of reserve forests, land grabs by powerful actors, illegal encroachment of forests, etc. The study was conducted with a view to assessing the present scenario of the forest governance system based on five UN principles in Bangladesh which will be the driving force to the successful implementation of the REDD+. The study was conducted in Rangamati, Madhupur, and Sreemangal, through focus group discussion, key informants interview, and an online survey. The study shows that lack of transparency, accountability, and integrity is one of the main underlying drivers of deforestation and forest degradation. Restriction to accessing reports on fiscal activities, lack of laws and regulation concerning to public funds, lack of independent institution, ineffective monitoring and testing systems, and inadequate detection, investigation, and prosecution practices, etc. enhance the corruption in the forestry sector and the hindrances of effective REDD+ implementation in Bangladesh. The study suggested taking legal protection, engaging civil society and improving the organizational structures of the forest department to check the corruption in the forestry sector of Bangladesh.The Chittagong Univ. J. Sci. 40(1) : 148-177, 2019